Association between Antibiotic Resistance with Duration of Hospitalisation in Diabetic Foot Ulcer Inpatient at Internal Ward in Dr. Soetomo General Hospital (Medico Legal Update, 2021)
Introduction: Diabetic Foot Ulcer (DFU) are microvascular and macrovascular complications fromdiabetes and has potential pathological risks including infection, ulceration, and deep tissue damage andis associated with neurological abnormalities, peripheral arterial disease, and metabolic complications inthe lower extremities. Diabetic foot injury is an infection of several pathogenic microorganisms that causetissue damage, if the infection is not handled properly then the wound will worsen and have an impact onamputation. Those pathogenic microorganisms could be a mono-microbial infection or a poly-microbialinfection and those infections could be multi-drug resistant organisms (MDRO).Objective: To analyse the association between antibiotic resistance and the duration of the hospitalisation indiabetic foot ulcer patient at Dr. Soetomo General Hospital.Method: This study is a cohort retrospective study that reviews medical records of all diabetic patients withdiabetic ulcer that was admitted into Dr. Soetomo General Hospital.Result: In Dr. Soetomo General Hospital the average duration of hospitalisation is 11.48 days. The species thatcaused the most infection under the category of gram-positive organisms are Enterococcus faecalis (7.8%),Staphylococcus aureus (5.2%) and Staphylococcus haemolyticus (3.9%). In the gram-negative category ofbacterial species, Proteus mirabilis (10.5%), Acinetobacter baumannii (9.8%) and Escherichia coli ESBL(8.5%) Patients had a high resistance towards is Cephazolin with a rate of 85.5% followed by Ampicillinwith 83.2% and Tetracyclin with 82.0%. Piperacillin-tazobactam (p-value 0.045) and Ceftazidime (p-value0.046) showed an association between antibiotic resistance and duration of hospitalisation. All patientspresented with MDRO and 35 (29.7%) were poly-microbial infectionConclusion: There is an association between antibiotic resistance and duration of hospitalisation forPiperacillin-tazobactam and Ceftazidime as well as 100% of patient presented with Multi-drug resistantorganism. Clinicians should refer to the periodic report from the internal ward on dominant species foundand antibiotic resistance more.